The effects of Hylocereus polyrhizus and Hylocereus undatus on physiocochemical, proteolysis, exopolysaccharides production, and therapeutic properties of yogurt / Khairul Hazmi bin Zainoldin - Zainoldin, Khairul Hazmi (2012)
Yogurt is generally recognized as a healthy and multifunctional food. It is a coagulated milk product obtained from the lactic acid fermentation by the action of Lactobacillus bulgaricus and Streptococcus thermophilus. In this present studies, dragon fruit Hylocereus polyrhizus and Hylocereus undatus extract was added in milk and their effects during yogurt fermentation were investigated. The changes in pH and Titratable Acidity (TA) were measured during fermentation and after 14 days of storage at 4°C. The yogurt extracts were subsequently analysed for their syneresis, proteolysis, peptide content, total phenolic content, antioxidant activities, inhibitory activities on α-amylase and α-glucosidase, presence of exopolysaccharides (EPS) and organoleptic properties. pH values for both dragon fruits yogurt showed significant reduction while TA showed higher percentages compared to plain-yogurts during fermentation and after 14 days of storage. Syneresis in yogurt (52.93%) also has been increased (p>0.05) with the addition of H. polyrhizus (57. 19-63.16%) and H. undatus (57.76-70.32%) compared to control (52.93%). The total phenolic content (TPC) in both dragon fruits yogurt (36.44-64.43ugGAE/ml) showed a greater increase (p<0.05) than plain yogurt (20.25ugGAE/ml). The addition of dragon fruits also increased (24.97-45.74%; p<0.05) antioxidant capacity compared to plain yogurt (19.16%). The peptides content in both dragon fruit yogurts were not different (p>0.05) from plain yogurt. Higher inhibitory activities (p<0.05) on α-amylase (17.30-52.20%), α-glucosidase (8.70-34.02%) and EPS production (214-738mg/L) in dragon fruit yogurts than in plain-yogurts were recorded (19.70%, 9.21%, and 181mg/L respectively). H. polyrhizus showed the highest score for visual appearance (7.77), aroma (5.9) and sweetness (4.22) while plain yogurt showed highest scores for body texture (6.81), sourness (7.13) and overall taste (5.45). In conclusion, the addition of H. polyrhizus and H. undatus in yogurt gave enhanced effects on physicochemical, therapeutic properties, production of EPS and organoleptic properties in yogurt.